The Impact of Green Accounting on Firm Value: The Mediating Role of Company Growth - David Seand Rafael Lubis; Meilda Wiguna; Nur Azlina (APSSAI ACCOUNTING REVIEW, 2025)
Research aims: This study examines the effect of green accounting on firm value with company growth as a mediating variable. The increasing demand for corporate sustainability has encouraged firms to integrate environmental considerations into their accounting practices. Design/Methodology/Approach: Using a quantitative research approach, this study analyses secondary data obtained from companies that implement green accounting practices. The data are analysed using mediation analysis to evaluate both direct and indirect relationships among variables. Research findings: The results indicate that green accounting has a positive and significant effect on firm value. Furthermore, green accounting also positively influences company growth, thereby enhancing firm value. The mediation test reveals that company growth partially mediates the relationship between green accounting and firm value. These findings suggest that implementing green accounting not only strengthens corporate growth but also increases firm value by improving stakeholder trust and long-term sustainability performance. Theoretical contribution/Originality: This study contributes to the literature on sustainable accounting by providing empirical evidence on the strategic role of green accounting in enhancing firm value.